An Agile systems development approach for enhancing e-Government user adoption - Lehasa, Odifentse Mapula-e (Rhodes University, Faculty of Commerce, Department of Information Systems, 2019)
The expansion of technological developments in all areas of society has seen governments taking advantage of new technologies to enhance public service delivery, disseminate information and promote participation by the public in government decision-making. This phenomenon is known as electronic government, or e-Government. However despite the socio-economic benefits inherent in the implementation of e-Government systems, an overwhelming number of government projects "“ particularly in developing countries "“ struggle to successfully implement e-Government systems. e-Government project failure is more pronounced in developing countries, with more than half of these projects either partially or completely failing. The failure of e-Government projects undermines government investments, as well as the potential socio-economic benefits that could be realised by the citizens. Arguably, while the failure or success of an e-Government project is attributed to a myriad of factors, low user adoption is one of the key factors that contribute to e-Government project failure. Therefore this thesis seeks to investigate the phenomenon of low e-Government user adoption and determine whether the use of an Agile system development approach can positively influence e-Government user satisfaction as well as buy-in and adoption. A Mixed-Methods, multi-case study approach was used through the perspective of Post-Positivism. The researcher examined four (4) South African e-Government projects "“ using an online questionnaire and in-depth interviews with members of the system development team "“ to determine whether the use of an Agile approach has merit in enhancing e-Government user adoption. The use of a Mixed-Methods approach allowed for data triangulation so as to verify the findings; while the use of multiple case studies enabled for cross-case analysis. The findings indicate that the use of Agile practices, as listed in the proposed Agile-informed User Engagement Guidelines, can ensure that the e-Government system developed meets user needs; and, that users are satisfied with, and make use of the e-Government system. However since most large e-Government projects make use of a traditional Waterfall development approach, it is recommended that the Agile practices (proposed guidelines) be incorporated into the structured Waterfall approach "“ to create a hybrid, or blended system development approach. In conclusion, the use of the proposed Agile-informed User Engagement Guidelines can enhance e-Government user adoption; and, subsequently, contribute towards nurturing the success of e-Government projects.
Keywords: Agile software development; Internet in public administration -- Developing countries